PENGARUH DIMENSI ZAKAT, MONEY ETHICS, DAN SOSIALISASI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK PADA UMKM DI SURABAYA - Edie Wijaya, Riesanti; Purwomiranti, Okti (Jurnal Riset Akuntansi Politala, 2023)
The objective of this study is to examine the influence of the zakat dimension, money ethics, and tax socialization on the level of compliance with compulsory personal tax among small and medium-sized enterprises in the Surabaya region. Basic research, which aims to improve and enhance current theories while also expanding knowledge, This study incorporates three distinct research variables, including tax socialization, money ethics, and the zakat component. The study employed a sample size of 100 respondents, who were selected from the population of taxable persons and individual perpetrators of the UMKM Islamic religion in Surabaya. The distribution of the sample was conducted using a questionnaire, which was administered to individuals registered with the KPP Pratama Surabaya. The present study used a multiple linear regression analysis for data analysis. The findings of the study indicate a significant positive correlation between taxation dimensions and tax socialization and compliance with tax duties. Conversely, the variable of money ethics exhibits a significant negative association with tax compliance.